Insights from a Rheumatic Heart Disease Registry in a Tertiary Centre in Sabah - Narwani Hussin,; Hafizah Jumat,; Wong, Mabelle; Liau, Siow Yen; Jeremy Robert Jinuin Jimin,; Beh, Boon Cong; Liew, Houng Bang (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Introduction Rheumatic heart disease is still endemic in developing countries and among the indigenous population in developed countries. However, there is no comprehensive data on rheumatic heart disease patients in Malaysia. The Cardiology Department of Queen Elizabeth ll Hospital (QEH ll), Sabah started this hospital-based registry in 2010. The objective of this analysis was to report the demographic profile, severity of disease, types of valve involvement and the practice of secondary prophylaxis among these patients. Methods This was a retrospective record review involved a three-year review of patients registered under the rheumatic heart disease registry in QEH ll, Sabah from December 2010 to November 2013. It included patients who attended the cardiology clinic who were diagnosed with rheumatic heart disease. Results A total of 627 rheumatic heart disease patients were registered over a period of three years. Mean age was 41 (16.2) year old, 67.5% were female, and 51.2% of the patients had severe valvular dysfunction with mitral regurgitation as the commonest valve affected (67.3%). There was an increasing trend in the percentage of patients receiving secondary prophylaxis (oral and intra-muscular) from the year 2010 to the year 2013 (23.2% and 67.6% respectively). Abnormal ECG, pulmonary regurgitation and not on any secondary prophylaxis were found to be associated with severe rheumatic heart disease. Conclusions Rheumatic heart disease is prevalent in Sabah. Most patients had severe form of valve dysfunction when diagnosed. Awareness and advocacy on secondary prophylaxis warrant immediate improvement.